2013
DOI: 10.1007/s00125-013-3107-6
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of flightless I improves wound healing and enhances angiogenesis in a murine model of type 1 diabetes

Abstract: Aims/hypothesis Skin lesions and ulcerations are severe complications of diabetes that often result in leg amputations. In this study we investigated the function of the cytoskeletal protein flightless I (FLII) in diabetic wound healing. We hypothesised that overexpression of FLII would have a negative effect on diabetic wound closure and modulation of this protein using specific FLII-neutralising antibodies (FnAb) would enhance cellular proliferation, migration and angiogenesis within the diabetic wound.Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 31 publications
1
41
0
Order By: Relevance
“…Decreasing Flii expression was associated with reduced inflammation as evidenced by fewer NIMP‐R14‐positive neutrophils and decreased proinflammatory cytokine production with reduced levels of TNF‐α, IL‐17A, IL‐22 and IL‐23 mRNA in the psoriatic‐like skin compared with both wild‐type and Flii Tg/Tg counterparts. Reducing cutaneous expression of Flii has also been observed to decrease inflammation in a diabetic wound model and to lessen further the severity of blistering in an immune‐mediated mouse model of epidermolysis bullosa acquisita . Previous studies have also shown that Flii overexpressing wounds have higher inflammatory cellular infiltrates in vivo , while in vitro studies have demonstrated that both intracellular and secreted extracellular Flii has the ability to alter inflammation and cytokine secretion via the TLR4 signalling pathway …”
Section: Discussionmentioning
confidence: 96%
“…Decreasing Flii expression was associated with reduced inflammation as evidenced by fewer NIMP‐R14‐positive neutrophils and decreased proinflammatory cytokine production with reduced levels of TNF‐α, IL‐17A, IL‐22 and IL‐23 mRNA in the psoriatic‐like skin compared with both wild‐type and Flii Tg/Tg counterparts. Reducing cutaneous expression of Flii has also been observed to decrease inflammation in a diabetic wound model and to lessen further the severity of blistering in an immune‐mediated mouse model of epidermolysis bullosa acquisita . Previous studies have also shown that Flii overexpressing wounds have higher inflammatory cellular infiltrates in vivo , while in vitro studies have demonstrated that both intracellular and secreted extracellular Flii has the ability to alter inflammation and cytokine secretion via the TLR4 signalling pathway …”
Section: Discussionmentioning
confidence: 96%
“…Representative digital images of wounds were captured and planimetric analysis of surface wound area and diameter were determined as described previously 18 (see online supplementary figure S5A-C). IVA337 (30 mg/kg and 100 mg/kg) did not influence the rate of wound closure ( figure 4A).…”
Section: Iva337 Does Not Affect Normal Wound Healingmentioning
confidence: 99%
“…IVA337 (30 mg/kg and 100 mg/kg) did not influence the rate of wound closure ( figure 4A). Histological analysis of day 7 and 14 wounds showed that the percentage of wound re-epithelialisation, 18 evaluated by measuring the length of the neoepidermis at day 7 after wounding remained unaffected in IVA337-treated mice compared with vehicle controls ( figure 4C). Our studies showed that the expression of PPARδ, which was undetected in unwounded human skin, is known for its role in epidermal maturation and wound healing, 29 was significantly higher in day 7 IVA337-treated wounds than in day 14 IVA337 wounds (see online supplementary figure S6A, B).…”
Section: Iva337 Does Not Affect Normal Wound Healingmentioning
confidence: 99%
“…In another example of injections by the intradermal route, work utilizing an animal model of Brown recluse (Loxosceles) spider bites showed that the local administration of specific antivenom Fab fragments was effective at attenuating the dermonecrotic lesion produced by spider venom when given up to 4 h after the bite (Gomez et al, 1999). In further examples, Flightless I (Flii) neutralizing antibodies injected intradermally around the margins of a surgical skin wound improved healing in porcine and murine models (Jackson et al, 2012;Ruzehaji et al, 2014) while antibacterial antibodies injected locally have demonstrated greater protection than systemic antibody in a guinea pig model of Treponema pallidum infection (Wicher et al, 1992). These results demonstrate further the effectiveness of the intradermal antibody delivery route in treating certain localized skin conditions.…”
Section: Intradermal Injectionsmentioning
confidence: 96%
“…The antibody was applied to the ulcers either as a 10 mg/mL solution covered with an adhesive sheet or as a gel formulation (0.45, 1 or 4.5 mg/g) under a hydrofiber dressing adhesive sheet. Although a cocktail containing additional healing agents (Attia et al, 2014;Burek-Kozlowska et al, 1994;Jackson et al, 2012;Kopecki et al, 2013;Pinho et al, 2014;Ruzehaji et al, 2014) may have an improved effect, this initial pioneering study is important in demonstrating the feasibility of the topical route in the clinical setting and again suggests that a high local concentration of anti-TNF favors prompt and definitive healing. Supporting evidence was recently provided by Teich & Klugmann (Teich & Klugmann, 2014), who reported a rapid improvement in refractory pyoderma gangrenosum, a reaction causing local skin ulceration, following the topical application of Infliximab in a sterile hydroxylethyl cellulose gel.…”
Section: Dermal Usementioning
confidence: 97%